Inside Back Cover: Synthesis, characterization, and biological applications of semiconducting polythiophene‐based nanoparticles (View 1/2021). Issue 1 (6th February 2021) - Zangoli, Mattia; Di Maria, Francesca
Abstract : In article number 20200086, the preparation, characterization and biological application of aqueous polythiophene based nanoparticles is reported by Francesca Di Maria and her colleagues. In particular, in vitro and in vivo bioapplications, in which thiophene‐based nanomaterials act as photoactuators ‐ i.e., as exogenous components capable of transforming a primary stimulus of light into a highly spatiotemporally resolved secondary stimulus able to alter cell's physiological functions ‐ will be presented.